2017
DOI: 10.1016/j.jtcme.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Improving glucose tolerance by muscle-damaging exercise

Abstract: Tissue damage is regarded as an unwanted medical condition to be avoided. However, introducing tolerable tissue damages has been used as a therapeutic intervention in traditional and complementary medicine to cure discomfort and illness. Eccentric exercise is known to cause significant necrosis and insulin resistance of skeletal muscle. The purpose of this study was to determine the magnitude of muscle damage and blood glucose responses during an oral glucose tolerance test (OGTT) after eccentric training in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…These findings indicated that slow-velocity eccentric-only resistance training improved glucose-related indicators and enhanced insulin sensitivity in T2DM patients. These results aligned with previous research conducted by Ho et al [12] However, slow-velocity eccentric-only resistance training may have limited effectiveness in improving lipid-related indicators (lipid control level) in T2DM patients. This study suggested that the unique slow-velocity eccentric-only resistance training model may have less effect on lipid interventions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings indicated that slow-velocity eccentric-only resistance training improved glucose-related indicators and enhanced insulin sensitivity in T2DM patients. These results aligned with previous research conducted by Ho et al [12] However, slow-velocity eccentric-only resistance training may have limited effectiveness in improving lipid-related indicators (lipid control level) in T2DM patients. This study suggested that the unique slow-velocity eccentric-only resistance training model may have less effect on lipid interventions.…”
Section: Discussionsupporting
confidence: 91%
“…[3,8,9] Members of the matrix metalloproteinases (MMPs) family, especially MMP-2 and -9, play a very important role in skeletal muscle ECM homeostasis [10,11] due to their ability to degrade skeletal muscle ECM collagen fibrillar proteins. [12] Many findings believe that the correlation between insulin resistance in skeletal muscle and collagen fiber deposition in ECM is attributable to the dysregulated expression of MMPs. Exercise is a universally accepted component of the nonpharmacologic treatment for T2DM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation